2009
DOI: 10.1001/archophthalmol.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Near Work, Outdoor Activity, and Myopia Among Adolescent Students in Rural China

Abstract: To study the associations between near work, outdoor activity, and myopia among children attending secondary school in rural China.Methods: Among a random cluster sample of 1892 children in Xichang, China, subjects with an uncorrected acuity of 6/12 or less in either eye (n=984) and a 25% sample of children with normal vision (n=248) underwent measurement of refractive error. Subjects were administered a questionnaire on parental education, time spent outdoors, and weekly time spent engaged in and preferred wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
3
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 39 publications
13
124
3
6
Order By: Relevance
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 90%
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 90%
“…60 Near work was also shown not to be associated with myopia in several other studies. 61,62 In a 5-year follow-up longitudinal study on 1318 children aged 6-14 years, hours per week spent reading or using a computer did not differ between the groups before myopia onset. Studying and TV watching were also not significantly different before myopia onset.…”
Section: Near Workmentioning
confidence: 95%
“…In some of the report it is mentioned that near work lead to myopia progression but certain studies also shows that myopia progress not only due to near work but also having association with intensity and duration of work. [7,8,9,10,11,12] Accommodation convergence have been suggested as the reasons sons for the development of myopia. If accommodation played a significant role in myopic progression .…”
Section: IImentioning
confidence: 99%